Distortions of the Hero: Felix Krull and Cú Chulainn. (3rd April 2018) - Sayers, William
Abstract : A significant amount of the graphic detail of the feigned epileptic seizure before the military review board in Thomas Mann's Die Bekenntnisse des Hochstaplers Felix Krull is traced to Ernst Windisch's German translation of the medieval Irish epic, The Cattle-raid of Cooley, from 1905, the same year that Mann appears to have begun work on the novel. The hero Cú Chulainn undergoes a pre-battle physical transformation accompanied by martial fury, in which the key Irish word is 'ríastrad', 'Verzerrung' in Windisch's rendering, the very concept with which Mann's description begins ('Mein Gesicht verzerrte sich'). This archaic shape-shifting sets the stage for the many additional instances of overt and covert dualities, and manipulated identities throughout the novel.